Pelatihan pengenalan dasar-dasar komputer bagi anak SD di Desa Nekbaun-Amarasi Barat - Taku Neno, Khatrin Juliani (Devotion: Jurnal Pengabdian Masyarakat, 2024)
Basic ability to operate a computer is an essential skill in the digital era, especially for elementary school children. Early introduction to technology not only improves logical thinking skills and access to information, but also prepares children for a future that is increasingly dependent on technology. However, there is a gap in access to computer education, especially in areas with limited facilities and resources, such as in Nekbaun-Amarasi Barat Village. Therefore, this service activity was carried out with the aim of reducing the digital divide through a training program to introduce computer basics for elementary school children in Nekbaun-Amarasi Barat Village. This training was carried out for three consecutive days, using lecture, discussion, question and answer, demonstration and practice methods. The results of service activities show that this training is effective in improving children's basic technical skills in operating computers. Apart from that, this program has also succeeded in increasing the awareness of parents and teachers about the importance of digital literacy. Thus, this program provides short-term benefits in the form of improving technical skills and long-term impacts by opening up more opportunities in education and future careers for children. This service activity emphasizes the importance of basic technology introduction programs to support the creation of a more technologically literate society and reduce the digital divide in remote areas.